THE ADAPTATION EXPERIENCE OF NEWLY RESIDENT ELDERLY PEOPLE IN NURSING INSTITUTIONS: A QUALITATIVE STUDY - Fan, Youyou (LIFE: International Journal of Health and Life-Sciences, 2024)
Objective: This study aimed to understand the experience and feelings of the newly admitted elderly in nursing institutions in the process of adaptation, in order to provide a reference for promoting the adaptation of the newly admitted elderly to life in institutions. Method: The phenomenological research method in qualitative research was used to conduct semi-structured interviews with 12 newly admitted elderly residents in three elderly care institutions in Zhengzhou, Xinzheng and Luoyang in Henan Province from November 2022 to July 2023 using the purposive sampling method, and the data were collated and analyzed by Colaizzi analysis. Outcomes: After data analysis, three themes were extracted: positive experience (including: Diet and daily life are guaranteed; Basic medical needs are met; Entertainment activities are abundant), negative emotion and experience(including: The sadness of leaving home; Complex interpersonal relationships; Worry about the state of the economy）, and the need for adaptation（including: Improve emotional and social support; Strengthen organizational management; Insufficient interaction） Findings: We found that the elderly had positive and negative living experiences in the early stage of living in nursing institutions. Some of the needs of the elderly are not met, and they also face adjustment problems such as emotional support, lack of social support, heavy psychological burden, difficulty in integrating into institutional life, and establishing new interpersonal relationships. Future scope: In the follow-up research, we can start from improving the elderly's self-cognition, enhancing social support, and promoting the interaction between the elderly and their peers, family members and caregivers, to formulate personalized intervention strategies to solve the problem of maladjustment in the early stage of the elderly living in nursing institutions and improve the quality of life.